Pengembangan Produk Ukir Berbasis 3 Dimensi untuk Mesin CNC - Okta Andrica Putra (Jurnal KomtekInfo, 2020)
A development has been carried out on carving Minangkabau motifs using a CNC machine by making 3D designs using aspire vector 8.5 software. The examiner was carried out on three Minangkabau motif carvings, namely kaluak nails, itiak back patang and aka cino saganggang. Tests were carried out with a work media size of 25cm x 15cm made of multiplex, MDF and wood. The average time for kaluak nail carving is 40 minutes, while the manual for beginner carvers is 2 to 3 months. For the spelling of carving itiak back in time the average time needed is 15 minutes, if done manually for beginners it takes 1 month, and for Akkino Saganggang carving work it takes an average of 25 minutes, if done manually for 1 to 2 months.